The Effect of Live Streaming, Price Discounts, Product Reviews on Impulse Buying Behavior at Shopee E-Commerce - Nala Mutimmul Faidah; Rusdi Hidayat Nugroho (International Journal of Economics Development Research (IJEDR), 2024)
Online shopping is a familiar activity. Currently, most consumers prefer to shop online in e-commerce rather than shopping directly. This is influenced by the many benefits obtained when shopping online. Currently, live streaming is being intensively carried out by sellers to promote their products. Like the live streaming feature in the shopee application, this feature spoils its consumers, namely by shopping when live streaming takes place consumers will get discounts and free shipping vouchers. This research is a study of the effect of live streaming, discounts, product reviews on impulse buying behavior in shopee e-commerce. This study uses associative research and the research approach used is a quantitative approach. While the sempel in this study was drawn using purposive sampling method with a total sempel of 200 respondents. The results of this study indicate that live streaming, price discounts, and product reviews simultaneously have a significant and significant effect on impulse buying on shopee e-commerce users in Surabaya. Live streaming and discount variables have a positive and significant effect on impulse buying variables because by viewing live streaming videos, customers know the details of the products being sold and get discount vouchers that increase customer interest in impulse buying. Meanwhile, the product review variable has a negative and insignificant effect on the impulse buying variable because customers know the quality of the product through previous customer responses.